دور الرقابة البيئية للحد من تلوث مياه الشرب (Journal of Accounting and Financial Studies ( JAFS ), 2011)
Targeted research to find control procedures to reduce contamination of drinking water and whether the public water systems monitor the channels properly and it is free from all pollution to try to reduce the phenomenon of environmental pollution of drinking water and therefore its impact on improving the health status and economic development. Thus, the practical side took the proposed framework to reduce the contamination of drinking water in the province of Baghdad, and the role of environmental control to reduce this pollution and to eliminate the problem of providing drinking water in the countr.